Proton conductors solids, membranes, and gels--materials and devices - Colomban, Philippe (Chemistry of solid state materials, 1992)
Protonic conduction in liquid electrolytes is commonplace but is relatively rare in solids. There is much interest worldwide in proton conducting solids, both from the scientific aspect, as materials with novel properties, but also for their possible applications in high-density solid-state batteries, sensors and other electrochemical devices. This book gives a comprehensive review of proton conductors, including theory, techniques, the materials themselves and applications